Inquiry Learning in Physics in lower secondary school as a creative path of scientific insight (Pedagogical Horizons, 2018)
This article deals with inquiry learning in Physics as a potential teaching concept to trigger scientific insight in lower secondary school. In a first step, a theoretical thought construct is elaborated on the basis of literature. This construct combines inquiry learning arrangements with intrinsic motivation, creativity in art and science, flow, and scientific insight. Subsequently, a questionnaire was compiled and tested, comprising items of different thought construct described in literature. Therefore, the chosen group of items were translated into German and adapted to the speaking comprehension of pupils of lower secondary school. The results of this empirical study show significant evidence that convincingly suggest that inquiry learning arrangements, such as AuRELIA, allow for higher intrinsic motivation and a creative process in the pupils.
Keywords: inquiry learning; creativity; Physic lessons